Pengaruh Suku Bunga Deposito, Nilai Tukar dan Inflasi Terhadap Harga Obligasi Pemerintah yang Terdaftar di Bursa Efek Indonesia Periode 2011-2017 - Desi Nitasari (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2018)
The purpose of this study is to 1). To know the effect of deposit interest rate on government bond price, 2). To know the effect of exchange rate on the price of government bonds, 3) To know the effect of inflation on the price of government bonds, 4). To know the effect of deposit interest rate, exchange rate, and inflation simultaneously to government bonds. The method used in this study is multiple regression. While the data analysis methods used are classical assumption test, simple linear regression analysis, test of simple linear regression coefficient, multiple linear regression analysis, multiple linear regression coefficient test, coefficient of determination analysis. Based on the results of simple regression analysis analysis of deposit interest rates on government bond prices obtained sig value. amounted to 0.342> 0.05, so it can be concluded that there is no effect of deposit rates on the price of government bonds listed on the Indonesia Stock Exchange period 2011-2017. From the results of simple regression analysis of the exchange rate against the price of government bonds obtained sig value. amounted to 0.060> 0.05, so it can be concluded that there is no effect of exchange rate on the price of government bonds listed on the Indonesia Stock Exchange period 2011 -2017. From the results of simple regression analysis of inflation analysis on the price of government bonds obtained sig value. amounted to 0.046 <0.05, so it can be concluded that there is inflationary influence on the price of government bonds listed on the Indonesia Stock Exchange period 20112017. From the results of simultaneous testing known significance value of 0.047. Because the probability value of sig nificance of 0,047 <0,05 can be interpreted that there is influence of deposit interest rate, exchange rate, and inflation simultaneously to government bond price listed in Bursa Efek Indonesia period 2011-2017.